Tanzania : A Simple Teacher Incentive System Can Improve Learning - World Bank (World Bank, Washington, DC, 2020)
Tanzania devotes about one-fifth of government spending to education, focusing much of the funding on expanding school access. Primary school enrollment rates have surged, yet the quality of education services and learning outcomes remain poor, with only 38 percent of children aged 9–13 able to read or do arithmetic at the second grade level. Teachers play a critical role in helping children learn, but in Tanzania, many do not show up to teach. Poor motivation and lack of accountability have contributed to the high absenteeism and commensurate loss of instructional time. One way to strengthen teacher motivation and management is through performance pay. Teacher incentive schemes link bonuses or other rewards to specific targets, whether outputs (e.g., verified classroom presence) or outcomes (e.g., student test score improvement). Performance pay can help achieve learning results at low cost compared to teacher base salaries. In Tanzania, the Results in Education for All Children (REACH) Trust Fund supported a randomized control trial comparing two types of teacher performance pay systems and their effect on early grade learning.